2016
DOI: 10.1111/all.12815
|View full text |Cite
|
Sign up to set email alerts
|

‘Real-life’ effectiveness studies of omalizumab in adult patients with severe allergic asthma: systematic review

Abstract: We reviewed 24 'real-life' effectiveness studies of omalizumab in the treatment of severe allergic asthma that included 4117 unique patients from 32 countries with significant heterogeneity in patients, clinicians and settings. The evidence underscores the short-and long-term benefit of anti-IgE therapy in terms of the following: improving lung function; achieving asthma control and reducing symptomatology, severe exacerbations and associated work/school days lost; reducing healthcare resource utilizations, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 53 publications
14
86
0
8
Order By: Relevance
“…In fact, Omalizumab (Xolair®) is a recombinant DNA-derived humanized monoclonal antibody indicated as an add-on therapy in patients aged ≥ 6 years with severe persistent allergic asthma uncontrolled at treatment step 4 or 5 according to guidelines GINA (2). Omalizumab demonstrated to be efficacious both in adults and children (3)(4)(5). In particular, in real-life studies, anti-IgE therapy showed short-and long-term benefits in terms of improving lung function and quality of life, achieving asthma control and reducing symptomatology, severe exacerbations, healthcare resource utilizations, hospitalizations, emergency department visits and reducing or discontinuing other asthma medications thus confirming, complementing, and extending evidence from randomized trials (3,5).…”
Section: Introductionmentioning
confidence: 64%
“…In fact, Omalizumab (Xolair®) is a recombinant DNA-derived humanized monoclonal antibody indicated as an add-on therapy in patients aged ≥ 6 years with severe persistent allergic asthma uncontrolled at treatment step 4 or 5 according to guidelines GINA (2). Omalizumab demonstrated to be efficacious both in adults and children (3)(4)(5). In particular, in real-life studies, anti-IgE therapy showed short-and long-term benefits in terms of improving lung function and quality of life, achieving asthma control and reducing symptomatology, severe exacerbations, healthcare resource utilizations, hospitalizations, emergency department visits and reducing or discontinuing other asthma medications thus confirming, complementing, and extending evidence from randomized trials (3,5).…”
Section: Introductionmentioning
confidence: 64%
“…In patients with severe allergic asthma, the add-on treatment with omalizumab has been shown to reduce the risk of exacerbations [113117], the asthma symptoms [113,114,116,118], and the use of OCS [118] and ICS [115], as well as to improve the quality of life and lung function [113,114,116], without significant safety concerns. These beneficial effects of omalizumab first shown in randomized clinical trials have been confirmed in longer term real-life studies [119121], and appear to be independent on patients’ comorbidities [118]. …”
Section: Management Of Severe Asthmamentioning
confidence: 88%
“…However, a multidimensional approach, where treatable traits are identified and targeted is being suggested [139]. This includes addition of LAMA in patients with fixed airflow obstruction, PDE4 inhibitors in patients with significant sputum production and exacerbations, smoking cessation programs, and pulmonary rehabilitation in patients with exertional dyspnea [119]. …”
Section: Management Of Severe Asthmamentioning
confidence: 99%
“…Данные о клинической эффективности и безопасно-сти ОМ обобщены в ряде обзоров, в которых подробно анализируются результаты как рандомизированных кон-тролируемых исследований (РКИ), так и проведенных в условиях реальной практики [3,4,10,11]. В нескольких РКИ на крупных выборках больных (взрослых и детей) с тяжелой АБА, у которых терапия высокими дозами инга-ляционных кортикостероидов (ИКС) в сочетании с дли-тельно действующими бета-агонистами (ДДБА) оказалась неэффективной, было убедительно показано, что допол-нительное лечение ОМ улучшает контроль симптомов астмы, качество жизни пациентов, сокращает количество обострений, в том числе тяжелых.…”
Section: лечение тяжелой астмы роль омализумаба при аллергической баunclassified